N-heterocyclic carbene-catalyzed [3+4] cycloaddition and kinetic resolution of azomethine imines - Wang, Ming (2014)
The first N-heterocyclic carbene (NHC)-catalyzed [3+4] cycloaddition of azomethine imines and enals is disclosed. Oxidative catalytic remote activation of enals affords 1,4-dipolarophile intermediates that react with 1,3-dipolar azomethine imines to generate dinitrogen-fused seven-membered heterocyclic products with high optical purities. Our approach also provides effective kinetic resolution of azomethine imines, in which the substrate chiral center that is remote from the NHC catalyst can be well resolved.